City, cholera, and COVID: A reading mediated by religiosity and science - Carlos E. Flores-Rodríguez; Luis Fajardo-Velázquez; Rosa María López-Nanco (Íconos, 2023)
On its way to liberalism and, above all, in relation to the difficulties that characterized this moment, the 19th century was fundamental in the configuration of the societies of Mexican cities and, in particular, of peripheral neighborhoods. This process is discussed in this article from a phenomenological and hermeneutic position and with ethnographic and historiographic tools. It considers the cases of the vice-royal neighborhoods of Analco and La Luz in the baroque city of Puebla. Historical factors are described that shaped its processes during a public health emergency. It is shown that the everyday life of its inhabitants had a dual character, mediated by religiosity and science. Thus, the streets functioned and still do function as the neighborhood center, the symbolic site of this syncretism and the site for neighborhood tactics in the protective search for a sense of identity. Also, the eventual and the permanent are found in the streets, where space becomes where one is and lives, as the symbol of attachment and belonging. The relevance of the text lies in the fact that it offers a privileged testimonial position for understanding what was done and what was understood during a disruptive event like COVID-19 from a social and collective lens. In addition, this text contributes to documenting the origin of new elements that add to existing immaterial heritage.